Penerapan Gerak Imitasi Lingkungan dalam Metode Penciptaan Tari Anak-Anak di SDN 21 Limo Kaum - Raizha Putri Yuda; Sri Meiweni Basra; Hardi Hardi; Yan Stevenson (INDO PUBLISHING, 2026)
Conventional dance instruction at SDN 21 Limo Kaum tends to be monotonous and lacks exploration, limiting children's creativity. Environmental imitation movement methods, such as imitating the movements of chickens, birds, rabbits, and cats, leverage children's natural curiosity to create relevant and enjoyable dances. This study aims to describe the application of imitation movement through environmental observation in the process of children's dance creation. It focuses on the exploration, improvisation, composition, and evaluation stages to optimize student engagement. A qualitative approach was used, including observations, interviews with teachers and principals, and documentation at SDN 21 Limo Kaum, Tanah Datar Regency. Primary data from the field were supplemented by literature studies for in-depth analysis. This method successfully went through four stages, producing creative, expressive, and contextual dances, increasing participation and environmental awareness. Permanent integration into the arts curriculum is recommended for children's holistic development.